Temple-Baraitser Syndrome and Zimmermann-Laband Syndrome: one clinical entity?. Issue 1 (December 2016) - Mégarbané, André; Al-Ali, Rashid; Choucair, Nancy; Lek, Monko; Wang, Ena; Ladjimi, Moncef; Rose, Catherine; Hobeika, Remy; Macary, Yvette; Temanni, Ramzi; Jithesh, Puthen; Chouchane, Aouatef; et al.
Abstract Background KCNH1 encodes a voltage-gated potassium channel that is predominantly expressed in the central nervous system. Mutations in this gene were recently found to be responsible for Temple-Baraitser Syndrome (TMBTS) and Zimmermann-Laband syndrome (ZLS). Methods Here, we report a new case of TMBTS diagnosed in a Lebanese child. Whole genome sequencing was carried out on DNA samples of the proband and his parents to identify mutations associated with this disease. Sanger sequencing was performed to confirm the presence of detected variants. Results Whole genome sequencing revealed three missense mutations in TMBTS patient: c.1042G > A inKCNH1, c.2131 T > C inSTK36, and c.726C > A inZNF517 . According to all predictors, mutation inKCNH1 is damagingde novo mutation that results in substitution of Glycine by Arginine, i.e., p.(Gly348Arg). This mutation was already reported in a patient with ZLS that could affect the connecting loop between helices S4-S5 ofKCNH1 with a gain of function effect. Conclusions Our findings demonstrate thatKCNH1 mutations cause TMBTS and expand the mutational spectrum ofKCNH1 in TMBTS. In addition, all cases of TMBTS were reviewed and compared to ZLS. We suggest that the two syndromes are a continuum and that the variability in the phenotypes is the result of the involvement of genetic modifiers.